2015
DOI: 10.1140/epjc/s10052-015-3478-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Newtonian anisotropic configurations

Abstract: In this paper we are concerned with the effects of an anisotropic pressure on the boundary conditions of the anisotropic Lane-Emden equation and the homology theorem. Some new exact solutions of this equation are derived. Then some of the theorems governing the Newtonian perfect fluid star are extended, taking the anisotropic pressure into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…A Newtonian approach is sufficient to study stellar structures in a comparatively low-density regime. However, in the case of compact stellar structures in the high-density regime, a general relativistic treatment is necessary, and the impact of anisotropy cannot be neglected while modelling such systems, see for example [1][2][3][4] and references therein. Ruderman [5] and Canuto [6] observed that material distribution in the highly dense core of a compact star might exhibit unequal stresses.…”
Section: Introductionmentioning
confidence: 99%
“…A Newtonian approach is sufficient to study stellar structures in a comparatively low-density regime. However, in the case of compact stellar structures in the high-density regime, a general relativistic treatment is necessary, and the impact of anisotropy cannot be neglected while modelling such systems, see for example [1][2][3][4] and references therein. Ruderman [5] and Canuto [6] observed that material distribution in the highly dense core of a compact star might exhibit unequal stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Following [3], we assume that the presence of ∆ does not change the forms of isotropic Lane-Emden equations and it only modifies the coefficients of these equations. To do this, noting equation (18), we introduce a constant m such that (hereafter we set c = 1): 2q 0 (n + 1)dθ − 4∆ rρ 0 θ n dr = 2q 0 (m + 1)dθ (39)…”
Section: An Exact Solutionmentioning
confidence: 99%
“…The effect of anisotropy can be studied both in Newtonian gravity and General Relativity. For the configurations with not extremely high densities, the presence of anisotropy factor has been discussed in Newtonian regime [1,2,3] and otherwise general relativity must be used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the more general hydrostatic equilibrium equations, considering pressure anisotropy, demonstrates that anisotropy can have a fundamental effect on the maximum equilibrium mass and gravitational surface red-shift [8][9][10]. At not very high densities, the effect of anisotropy can be analyzed in the context of Newtonian gravity [11,12]. At higher densities i.e., when ρ ≥ 10 15 g/cm 3 , both the GR effects and the relativistic effects become more important [7,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%